Immunohistochemical expression of Ki-67 in invasive breast carcinoma and its correlation with prognostic parameters - Jain, Rashmi; Malik, Reeni; Trichal, V.K.; Jain, Ankit; Bakna, Minu (International Journal of Medical Research and Review, 2016)
Background: Ki-67 expression is strictly associated with cellular proliferation and is an excellent marker for determining the growth fraction of a given cell population. It may be considered as alternative to mitotic counts in grading schemes and as a single parameter that can be used in fine needle aspirates and small biopsies. The aim of this study was to evaluate proliferative fraction of Ki67 expression in invasive breast carcinoma and to find out the correlation between Ki67 expression and clinico-pathological prognostic factors such as tumor size, lymph node status, histological grade and Nottingham prognostic index. Materials and Methods: Seventy cases of infiltrating ductal carcinoma breast were studied. Immunohistochemistry using the anti-Ki-67 antibody [MIB-1] was performed on all cases and Ki-67 staining was categorized as low and high grade. Result: High expression of Ki-67 was found in 71.05% cases of breast tumor with positive lymph node metastasis and 92.31% cases of Grade III tumor. Ki-67 expression was significantly associated with nodal status (p<0.0001) and poorly differentiated tumor (p<0.0001). Although, Ki-67 expression was associated with tumor size, but their correlation was not statistically significant (p= 0.065). Conclusion: High Ki-67 expression was associated with a higher grade of malignancy. Conclusively, proliferative activity determined by Ki-67 expression may reflect the aggressive behavior of breast carcinoma. Ki-67 detection provides valuable information about proliferative activity of cells so, it is necessary to combine this with other parameters for better prognosis.